Effect of Phenylephrine Provocation on Dispersion of Repolarization in Congenital Long QT Syndrome - Khositseth, Anant (Ann Noninvasive Electrocardiol, 2003)
Introduction: Syncope and sudden death are associated with sympathetic stimulation in LQT1 while LQT2 patients are more susceptible to arrhythmias during nonexertional states. Abnormal spatial (QTd)‐ and transmural (TDR)‐dispersion of repolarization may indicate increased arrhythmogenicity. This study compares the effect of phenylephrine on QTd and TDR in genotyped LQTS to control (C). Methods and Results: Seventeen LQT1, 12 LQT2, and 18 age‐ and sex‐matched normal controls received 2 mcg/kg of phenylephrine intravenously. At baseline and peak phenylephrine effect, BP, QT, RR, Bazett's QTc, precordial QTd (QTmax−QTmin), and T‐peak to T‐end (Tp‐e) intervals were determined blinded to the patient's clinical and genotype status. Baseline QT intervals and QTc were significantly longer in LQT1 and LQT2 compared to C. Baseline QTd and Tp‐e were greater in LQT2 than either LQT1 or C: QTd = 79 ± 29 ms (LQT2), 53 ± 26 (LQT1), and 45 ± 15 (C) and Tp‐e = 120 ± 30 ms (LQT2), 99 ± 20 (LQT1), and 90 ± 11 (C). Overall, phenylephrine exerted no significant effect on either QTd or Tp‐e except with subgroup analysis of symptomatic LQTS where LQT1 and LQT2 patients had a divergent response with TDR. Conclusions: Phenylephrine‐induced bradycardia decreased TDR in symptomatic LQT1 but increased TDR in symptomatic LQT2. The observed effects of phenylephrine are consistent with the protective effect of beta‐blocker in LQT1 and the increased arrhythmogenicity noted during nonexertional states in LQT2.